Evaluation of mRNA-1273 Covid-19 Vaccine in Children 6 to 11 Years of Age - Creech, C. Buddy; Anderson, Evan; Berthaud, Vladimir; Yildirim, Inci; Atz, Andrew M.; Melendez Baez, Ivan; Finkelstein, Daniel; Pickrell, Paul; Kirstein, Judith; Yut, Clifford; Blair, Ronald; Clifford, Robert A.; et al. (The New England journal of medicine, 2022)
In part 1 of a phase 2–3 trial, a 50-μg dose of mRNA-1273 vaccine was safe and immunogenic. In part 2, nearly 4000 6-to-11-year-olds received two doses of vaccine or placebo and were followed for a median of 82 days. The vaccine had mainly mild adverse effects and was immunogenic in 99%, similar to the results in 18-to-25-year-olds. Vaccine efficacy during a delta-variant period was 88%.